IMPLEMENTATION OF KLAUS'S CUSTOMER EXPERIENCE QUALITY CONCEPT ON INTENTION TO SWITCH NEXA INTERNET CUSTOMERS TO OTHER INTERNET PROVIDER - Cantika Dewi Purnama Putri; Ignatius Hari Santoso (SEAN Institute, 2023)
The development of information and communication technology business is increasing. Currently, human life is starting to shift to a life of pervasive computing, a life that places information technology as part of human life anytime and anywhere. This can be seen from the behavior of humans who are getting used to computers, the internet, and information technology. This research wants to see Switching Intention in terms of service quality and customer satisfaction. This research uses SmartPLS (Partial Least Square) to test the research hypothesis. The results of this study indicate that Peace Of Mind and Outcome Focus have a significant and positive effect on Switching Interntion. However, Customer Experience Quality, Product Experience, and Moment Of Truth are not able to have a significant effect on Switching Intention. Managerial implications in this study should improve service quality at low prices to increase customer loyalty and reduce switching intention of service users.